Peningkatan Keaktifan Belajar Fisika Peserta Didik melalui Penerapan Problem Based Learning - Yuni Erviyanti; Kaharuddin Arafah; Anis Nur (Universitas Negeri Makassar, 2022)
This article aims to determine the activities of students in teaching and learning activities on the subject of elasticity of solids after applying the Problem Based Learning model. This article is motivated by the lack of student activity during teacher teaching because usually the learning process only focuses on the teacher. Physics learning is considered important so that students are not passive and during learning takes place. The expected goals in this article are, among others, to increase student activity after the problem-based learning model is applied. The method used to describe problem-based learning activities is Classroom Action Research. The steps applied in this research is to carry out research stages such as planning, implementation, observation and reflection. The data collection technique is by recording events during learning and being observed by the teacher or implementing activities through learning videos which are then analyzed qualitatively. Based on the observations of the recordings and the teacher's experience, it can be concluded that students are more active during learning activities, including collaborating, asking questions, answering questions, and answering questions.